SIMULATING CROP YIELD, SOIL NITROGEN, AND ORGANIC CARBON IN NO-TILLAGE CROP SEQUENCES IN A SUBTROPICAL CLIMATE IN BRAZIL - Silva, Bruna de O. [UNESP]; Santos, Gustavo A. de A. [UNESP]; Santos, Miqueias G. dos [UNESP]; Morais Filho, Luiz F. F. [UNESP]; Faria, Rogerio T. de [UNESP] (Soc Brasil Engenharia Agricola, 2020)
Brazil stands out worldwide for its high grain production in areas of direct sowing. The objective of this study was to simulate and assess the relationship of soil organic carbon content and nitrogen, crop yield, and biomass of two crop sequences under the no-tillage system in a subtropical region of Sao Paulo, Brazil, using CSM-CROPGRO-Soybean and CSM-CERES-Maize models. The modeling was carried out considering the meteorological conditions of Jaboticabal, SP, Brazil. The treatments consisted of combining two summer crops (maize and soybean) with maize cultivation as a winter crop. The average biomass and productivity for corn were 15594 kg ha(-1) and 5996 kg ha(-1), respectively, and for soybeans they were 5905 kg ha(-1) and 3441 kg ha(-1), respectively. For soil organic carbon and nitrogen, a small variation was observed between years, and in addition there was a decline in their levels after a year with low biomass production. In our study, the RMSE and MAPE values between the observed and simulated productivity by the model were 2.21 kg ha(-1) and 44.24%, respectively. The analysis of main components for the cultivation of corn explained 83.9% of the variability, and for the cultivation of soy, 93.5%. Among the tested models, the CROPGRO was the one with the best accuracy.
Keywords: CSM-CROPGRO; CSM-CERES-Maize; Conservationist tillage; Greenhouse gas emission